The Tudors. The complete second season [videorecording (DVD)] - Hirst, Michael, 1952-; Morris, Trevor, 1970- (Showtime Entertainment, 2008)
After failing to have his marriage to Katherine annulled, Henry appoints himself the head of the Church of England. Anne Boleyn insists that Henry remove the Queen from the picture. A royal visit to France finally prompts Anne to consummate her relationship with Henry. After failed attempts to have his marriage annulled, Henry's patience finally wears out and he marries Anne in secret. The king and new queen are disappointed that their first child is a girl, whom they christen Elizabeth.